Horizontal Transfer of Different erm(B)-Carrying Mobile Elements Among Streptococcus suis Strains With Different Serotypes - Chen, Li; Huang, Jinhu; Huang, Xinxin; He, Yuping; Sun, Junjie; Dai, Xingyang; Wang, Xiaoming; Shafiq, Muhammad; Wang, Liping (Frontiers in Microbiology, 2021)
Macrolide-resistant Streptococcus suis is highly prevalent worldwide. The acquisition of the erm(B) gene mediated by mobile genetic elements (MGEs) in particular integrative and conjugative elements (ICEs) is recognized as the main reason for the rapid spread of macrolide-resistant streptococcal strains. However, knowledge about different erm(B)-carrying elements responsible for the widespread of macrolide resistance and their transferability in S. suis remains poorly understood. In the present study, two erm(B)- and tet(O)-harboring putative ICEs, designated as ICESsuYSB17_rplL and ICESsuYSJ15_rplL, and a novel erm(B)- and aadE-spw-like-carrying genomic island (GI), named GISsuJHJ17_rpsI, were identified to be excised from the chromosome and transferred among S. suis strains with different serotypes. ICESsuYSB17_rplL and ICESsuYSJ15_rplL were integrated downstream the rplL gene, a conserve locus of the ICESa2603 family. GISsuJHJ17_rpsI, with no genes belonging to the conjugation module, was integrated into the site of rpsI. All transconjugants did not exhibit obvious fitness cost by growth curve and competition assays when compared with the recipient. The results demonstrate that different erm(B)-carrying elements were presented and highlight the role of these elements in the dissemination of macrolide resistance in S. suis.